Comparative Genomic Analysis of Two Monokaryons of Auricularia heimuer Hei29 - Fengli Wang; Chuang Han; Jiechi Zhang; Piqi Zhang; Xiaojia Zhang; Xin Yue; Yanshu Zhao; Xiaodong Dai (Journal of Fungi)
Auricularia heimuer is a valuable traditional Chinese fungus used as food and medicine. Hei29 is a strain derived from wild A. heimuer through systematic domestication and selection. It has been the primary A. heimuer variety in Northeast China for 30 years and offers the advantages of high yield, good commercial property, and stable traits. This study used protoplast nucleation on Hei29 to produce two amiable and paired monokaryons, Hei29-D1 and Hei29-D2. The genome of Hei29 was sequenced utilizing the Illumina PE150 and PacBio Sequel sequencing platforms. Hei29-D1 and Hei29-D2 had genomic sizes of 47.54 Mb and 47.49 Mb, GC contents of 56.95% and 56.99%, and an N50 of 2.37 Mb and 4.28 Mb, respectively. Hei29’s genome possessed two phytoene synthase (PSY) protein genes, one of which—PSY encoded by g894—has a transmembrane domain. The phylogenetic tree showed that Hei29 shared the closest evolutionary relationship with Auricularia subglabra TFB-10046 SS5. Collinearity analysis showed that the correlation between the two monokaryons was as high as 90.81%. Cluster analysis revealed that Hei29 contains 12,362 core genes, 223 unique genes in Hei29-D1, and 228 unique genes in Hei29-D2. This study is the first to sequence two related and paired monokaryons from A. heimuer, which is critical for fully understanding the genetic composition and information of the characteristic strain of A. heimuer in Northeast China. It establishes the data and theoretical foundation for gene mining, usage, and molecular breeding. It further promotes the genetic breeding and active substance utilization of A. heimuer.